Degradação ambiental: uma análise dos problemas causados pela formação de um lixão nas proximidades do rio Pirateua, Augusto Corrêa - PA - BRITO, Adailson Lima (2019)
In the face of environmental problems the generation of solid waste is consolidated as one of the great challenges of concern on the part of society. As a result, the government has expressed to establish the correct management of this waste through the implementation of the Integrated Management Plan of the Solid Waste directed to municipalities in an attempt to minimize the damage caused by the problem of waste. In this context, actions involving the irregular disposal of solid waste, as well as the formation of the open dumpsite practiced irresponsibly should be curbed to preserve the environment. In this perspective, the research work of this analyzed the environmental problems caused by the formation of a garbage dump near of Pirateua’s community, located in Augusto Corrêa city. For this, data were collected through the application of a socioeconomic and environmental questionnaire directed to 18 families living in that community and on-site visit to survey the damage incurred. Thus, the work has identified several types of environmental degradation resulting from these actions on the site, as well as other derived from a mineral exploration activity which together are causing dissatisfaction to the residents and other problems arising from these actions.